Analysis of Monte Lemon (Citrus Limon) and Telang Flower (Clitoria Ternatea) Herbal Tea - Zira Azifa Ayska; Nurmahni Harahap; Halimatus Sakdiah (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Monte Herbal Tea is a tea made from lemon and Telang flowers, so from the combination of the two plants this herbal tea is named monte tea (lemon and Telang). In addition, this monte tea has many benefits such as increasing energy, refreshing the brain, and being able to increase body stamina. In SNI, in making this monte herbal tea I used the experimental method. Data processing is carried out by giving Monte tea that has been brewed to the panelists then after the tea has been tried the researcher starts giving the questionnaire to the panelists to fill in the appropriate statements according to the panelists regarding herbal tea as in the attachment, then after giving the questionnaire and it has been filled in by the panelists, then the researcher starts processing the data as in the research results. This tea is made from main ingredients that have many benefits for the health of the body. Such as lemon fruit that can contribute Vitamin C to our body, and Telang flowers that can reduce the risk of hypertension and heart disease. In this study there are several elements that were tested, namely, color, texture, aroma, and taste. In this study requires panelists totaling 10 people.